Is conceptual vagueness an asset? Resilience research from the perspective of philosophy of science - Sebastian Strunz (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
I analyze the research on social-ecological resilience from the perspective of philosophy of science in three steps. First, I explore to what degree resilience research exhibits conceptual vagueness. I find a wide spectrum of research, ranging from approaches relying on a concise conceptual framework to the perspective of resilience thinking, which builds on a cluster of vague concepts. Second, I set out the methodological arguments in favor and against conceptual vagueness. Merging both strands of reasoning in the third step, I conclude that a trade-off between vagueness and precision exists, which is to be solved differently depending on the context of resilience research. In some contexts, resilience research benefits from conceptual vagueness while in othersit depends on precision. Specifically, I argue that in resilience thinking the trade-off might be enhanced by a coherent restructuring of the conceptual framework.
Keywords: 330; vagueness; philosophy of science; precision; resilience thinking; socialecological systems; Umwelt; Sozialökonomik; Wissenschaftstheorie